2022
DOI: 10.1123/jsr.2020-0315
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions Can Reduce Injury Risk in Athletes: A Critically Appraised Topic

Abstract: Clinical Scenario: Injury prevention programs are becoming standard practice for reducing sports-related injuries, but most programs focus on musculoskeletal elements. Psychological factors can be strong predictors of sports-related injuries and there is recent evidence that suggests psychological interventions can be effective at reducing injury risk. It is unclear if injury prevention programs that focus on psychological factors are an important inclusion for athletic trainers/therapists. Athletes can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…A recent review on the use of psychological interventions to reduce the risk of injury in athletes concluded that there is sufficient evidence supporting the use of psychological-based interventions by athlete support staff to reduce injury incidence among athletes. 10 Although Ivarsson et al 14 found that a group of athletes that completed mindfulness training suffered fewer injuries than the group that did not undergo mindfulness training, our study demonstrated that a single mindfulness practice the day before a practice or competition event significantly reduced the risk of injury. Taken together, there is evidence that after a single mindfulness activity, an athlete has a lower risk of injury.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent review on the use of psychological interventions to reduce the risk of injury in athletes concluded that there is sufficient evidence supporting the use of psychological-based interventions by athlete support staff to reduce injury incidence among athletes. 10 Although Ivarsson et al 14 found that a group of athletes that completed mindfulness training suffered fewer injuries than the group that did not undergo mindfulness training, our study demonstrated that a single mindfulness practice the day before a practice or competition event significantly reduced the risk of injury. Taken together, there is evidence that after a single mindfulness activity, an athlete has a lower risk of injury.…”
Section: Discussioncontrasting
confidence: 64%
“…Psychological and emotional stress and life stress were considered ‘absolutely essential’ by 35% and 41% of the participants, respectively. The relevance of ‘stress’ has been discussed in the training adaptation literature as well as that of sports injury occurrence and rehabilitation efficacy [ 13 , 32 , 33 ]. It is interesting to note that life stress received a higher rating even though it could be considered a subset of psychological and emotional stress.…”
Section: Discussionmentioning
confidence: 99%
“…Objective evidence suggests that psychological interventions can substantially lower injury risk [ 7 , 8 , 9 ]. Notably, stress management techniques, such as breathing exercises, cognitive restructuring, mindfulness, motor imagery, or seeking social support, have been demonstrated as being highly effective [ 7 , 10 , 11 , 12 ]. These techniques, many of them originally intended by sport psychologists to optimize performance in elite athletes, now aid junior athletes in performing at their best while also preventing injury and facilitating a safe return to competition after injury, if indicated.…”
Section: Introductionmentioning
confidence: 99%